-2(3x+5)-6(x)=

Simple and best practice solution for -2(3x+5)-6(x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x+5)-6(x)= equation:


Simplifying
-2(3x + 5) + -6(x) = 0

Reorder the terms:
-2(5 + 3x) + -6(x) = 0
(5 * -2 + 3x * -2) + -6(x) = 0
(-10 + -6x) + -6(x) = 0

Combine like terms: -6x + -6x = -12x
-10 + -12x = 0

Solving
-10 + -12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -12x = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -12x = 0 + 10
-12x = 0 + 10

Combine like terms: 0 + 10 = 10
-12x = 10

Divide each side by '-12'.
x = -0.8333333333

Simplifying
x = -0.8333333333

See similar equations:

| (-6x^2)+8x=0 | | -325=13x | | 5r^2=-32+28r | | 4=2.5x | | -5n+5+3n=-15 | | 6m+6=10m+24 | | f(1)=5-2(1) | | 7(4-9)=-26+6x | | 5(x+43)+-2=-2 | | -14+9x=11+8x | | (X*5)-16=3(X+10) | | (4x^2-6x+8)+(7x-3)=0 | | 4.2x-1.5=1.9x+7.7 | | -4(x+12)+9=-7 | | 16*x=64 | | p(x)=x^4-3x^3+18x^2-48x+32 | | -53-7x=55+2x | | 2x-39+-4x=3 | | 4t-5t=3 | | -42+9x=x+86 | | 4x+19=83 | | 5u-6=-21 | | 3(x+41)+8=50 | | 3.8r=-6 | | -29+6x=31+11x | | -2x-47+4x=-21 | | (x+14)(x-2)= | | 10x-45+12x=43 | | 3r(4r-5)=6(5r+8) | | -3y+10x=-5 | | P=11*3 | | -23-3x=-5x+15 |

Equations solver categories